Find accurate and reliable answers to your questions on IDNLearn.com. Discover detailed and accurate answers to your questions from our knowledgeable and dedicated community members.

Subtract the like terms to find [tex]f(x) - g(x)[/tex].

If [tex]f(x) = 3x^2 - 4x + 5[/tex] and [tex]g(x) = 2x^2 + 2[/tex], find [tex]f(x) - g(x)[/tex].

A. [tex]5x^2 - 4x + 7[/tex]
B. [tex]x^2 - 4x + 3[/tex]
C. [tex]-x^2 + 4x - 3[/tex]
D. [tex]x^2 - 4x + 7[/tex]


Sagot :

To find \( f(x) - g(x) \) where \( f(x) = 3x^2 - 4x + 5 \) and \( g(x) = 2x^2 + 2 \), follow these steps:

1. Arrange the expressions for \( f(x) \) and \( g(x) \):
[tex]\[ f(x) = 3x^2 - 4x + 5 \][/tex]
[tex]\[ g(x) = 2x^2 + 2 \][/tex]

2. Subtract the like terms of \( f(x) \) and \( g(x) \):
- \( x^2 \) terms: \( 3x^2 - 2x^2 = 1x^2 \)
- \( x \) terms: \( -4x \)
- Constant terms: \( 5 - 2 = 3 \)

3. Combine the results from step 2 to form the polynomial \( f(x) - g(x) \):
[tex]\[ f(x) - g(x) = 1x^2 - 4x + 3 \][/tex]

So, \( f(x) - g(x) \) is:

[tex]\[ \boxed{x^2 - 4x + 3} \][/tex]

Checking the choices:
A. \( 5x^2 - 4x + 7 \)
B. \( x^2 - 4x + 3 \)
C. \( -x^2 + 4x - 3 \)
D. \( x^2 - 4x + 7 \)

Thus, the correct answer is option [tex]\( \boxed{B} \)[/tex].